PENERAPAN METODE ACCELERATED LEARNING DALAM PEMBELAJARAN MATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP - Dina Damayanti; Jarnawi Afgan Dahlan; Nar Herrhyanto (Program Studi Pendidikan Matematika, FKIP Universitas Muhammadiyah Cirebon, 2018)
This research is motivated by the mathematical communication skills of students who are still low. The purpose of this experimental research is to find out whether the mathematical communication skills of students who get learning using the Accelerated Learning method are better than students who get learning using the expository method and to find out students' responses to learning using the Accelerated Learning method implemented. The population in this study were all grade VII students of SMP Negeri 29 Bandung, while the selected sample of 12 classes was class VII-B as the experimental class and class VII-A as the control class. The research design used was a pretest-posttest control group. The discussion used in this study is Triangle. The instruments used were tests of mathematical communication skills (pretest and posttest) and non-test instruments, namely questionnaires, observation sheets and daily journals. The results showed that the mathematical communication skills of students who get learning by using the Accelerated Learning method are better than students who get learning by using expository methods. In addition, almost all (96.57%) students gave positive responses to mathematics learning using the accelerated learning method.Keywords: Accelerated Learning, Mathematical Communication Skills.